School Head leadership qualities and school performance in the Pacific towns of Northern Samar - Emie Rose Adto-Morallos (Center for Humanities and Innovation Studies, 2022)
A correlational research design was employed to determine the relationship between the leadership qualities of school heads and the school performance in the 2019 National Achievement Test in the pacific towns of Northern Samar. The data were analyzed using frequency counts, percentage, mode, and Spearman rho correlation test at a .05 level of significance. Findings showed that the majority of the respondents are aged 30-34 years old, female, with at most ten years in the profession, hold a master's degree, have attended 11-20 seminars and conferences, and possess a very satisfactory level of leadership qualities in terms of challenging the people, inspiring people, enabling others to act, modeling the way, and encouraging people. Most schools in the pacific towns of Northern Samar scored average mastery in the national achievement test. However, no significant relationship was established between the leadership qualities of school heads and school performance on the national achievement test. Hence, local training workshops should be designed and conducted on the awareness of the leadership qualities of the school heads and teachers.